Frontispiece: In Situ Cyclization of Native Proteins: Structure‐Based Design of a Bicyclic Enzyme. Issue 35 (21st August 2018) - Pelay‐Gimeno, Marta; Bange, Tanja; Hennig, Sven; Grossmann, Tom N.
Abstract : Protein Engineering . In their Communication onpage 11164 ff., T. N. Grossmann et al. report on the generation of a bicyclic enzyme with a triselectrophilic linker, which leads to strongly increased stability towards thermal denaturation.